The Realization of Conversational Features in Massively Multiplayer Online Game Chat Entitled ‘Mafia City’ - Giovani, Wanda; Fitriati, Sri Wuli (Universitas Negeri Semarang, 2018)
The aim of this study is to describe and to explain the realization of conversational features in massively multiplayer online game chat entitled Mafia City. This study used a conversation analysis approach with a qualitative design. The focus of this study is the gamers’ interactions through the game chat. The instrument of the research is I myself as the participant observer. Tables of specifications are the secondary instrument in the observation. The results of the study show that in Mafia City, the use of conversational features such as turn-takings, adjacency pairs, and repairs is possible. Even so, the realization of those features was not exactly similar compared to those in face-to-face conversation. The main problem was the disrupted turn-takings and adjacency pairs. For repairs, the most common type that appeared in the chat was self-initiated self-repair, while the most common pattern that occurred was replacement. Their occurrences were in consequence of the nature of online chat which is visually decontextualized. For jargons, the chatters are creative enough to create acronyms, contractions, and abbreviations freely. For the realization of extra-linguistic features, the chatters used emoticons as the result of the chatters’ creativity in dealing with the lack of prosodic features. These findings can be beneficial for the development of discourse study, especially in internet-based communication.